Thought Experiment between Revealed Theology and Narrative - Savojardo, Valentina (Religions, 2022)
The paper addresses the problem of the epistemic value of thought experiment, in revealed theology, insofar as it possesses a fundamental trait in common with fiction. Starting from Fehige’s proposal to reread St. Anselm’s ontological argument as a thought experiment of revealed theology and in the light of important differences between the use of scientific and theological thought experiments, it is possible, even in theology, to speak of an indirect or ‘reflexive’ nexus between thought and action. On the basis of this nexus, one can rethink the epistemic role of the theological thought experiment in relation to the art of narration that brings theological thought experiments and fiction closer together. However, it is always the context in which the thought experiment is considered that determines its value and role.